The role of negative age stereotypes and sociodemographic factors in the intention to leave among German university hospital nursing staff - Helaß, Madeleine; Greinacher, Anja; Müller, Andreas; Friederich, Hans-Christoph; Maatouk, Imad; Nikendei, Christoph (Inquiry, 2024)
Staff shortages are a global problem in the nursing profession. Negative beliefs about older workers may have detrimental effects on the development and performance capacity of an aging workforce. To date, little is known about the impact of age stereotypes and potential factors on nurses’ intent to leave (ITL). Therefore, the aim of our study was to assess intention to leave and potential predictors (eg, sociodemographic characteristics and age stereotypes) in a large representative sample of nurses in a German university hospital setting. A total of 423 nurses at the University Hospital of Heidelberg participated in a cross-sectional questionnaire study assessing sociodemographic data, age stereotypes using the “Beliefs About Older Workers” questionnaire, and participants’ intentions to leave and give up their profession. Questionnaires were returned by 423 nurses (13.7% response rate). The results revealed that negative age stereotypes were highly prevalent. Significant correlations between age and negative age stereotypes were found, indicating that the younger the nurses were, the more negative their age stereotypes were. Most nurses with negative age stereotypes had no intention to leave their profession; however, the majority of nurses could not imagine working in the profession until they retired. Despite the low response rate, the results of the current study suggest that organizational and societal measures to reduce age stereotypes should be directed at newcomers and young nurses to retain them in the profession in the long term.
Gesehen am 20.03.2025